Interventions targeting identity in adults with psychosis, severe mental illness, brain injury, or intellectual disability: a transdiagnostic scoping review - Kronemeijer, Uupke Elizabeth; Pijnenborg, Gerdina Hendrika Maria; Muthert, Johanna Karina; van Setten, Ellie Richtje Hennie; van der Meer, Lisette (Frontiers in Psychiatry, 2026)
ObjectiveDespite the extensive literature linking identity experiences with Severe Mental Illness (SMI), little is known about interventions specifically addressing identity in this population. This scoping review aims to explore the available literature on identity interventions whilst adopting a transdiagnostic approach. We provide an overview of intervention studies targeting identity or self-concept in individuals with psychotic spectrum disorders or severe mental illness (SMI), acquired brain injury (ABI), or intellectual disability (ID).MethodsA search was conducted across six databases for articles up to November 2025. Eligible studies were peer-reviewed and evaluated interventions for individuals with SMI, ABI, or ID. These interventions either focused upon identity or assessed outcomes specifically related to identity. Case studies, theoretical papers, and reviews were excluded. Both qualitative and quantitative data were summarized, emphasizing study approaches, intervention approaches, theoretical frameworks, outcomes and recommendations for future studies.ResultsA total of 35 studies were identified: 16 on SMI/psychosis, 17 on ABI, and 2 on ID. There was substantial heterogeneity across interventions. Interventions aimed to help individuals become more positive, develop complex identities, adjust to illness, reconstruct integrated self-narratives, and experience an empowered (social) identity. Participants learned through experience, social connection, self-reflection, and narrative- and cognitive restructuring.DiscussionThis review identifies several promising intervention elements for future research, as discussed in the paper. However, considering the limited number of studies, their heterogeneity, and the exploratory nature of this research, further investigation is required to build upon and expand existing approaches.